Spatial Organization of Genomes - Gheldof, N; Dekker, J (Current Genomics, 2004)
Analysis of whole genome sequences has revealed that genes constitute only a small fraction of the DNA. The function of the remaining part of the genome is still enigmatic. The role of chromosome structure in gene regulation and maintenance of genome stability is increasingly appreciated, which has led to the hypothesis that large parts of the genome may be dedicated to controlling the formation of specific chromosome conformations. Here we review recent advances in our knowledge of chromosome structure and nuclear organization. We describe possible mechanisms by which genomes encode their spatial conformation, such as the use of specific DNA sequence elements to set up local chromatin structures and the potential exploitation of more global sequence characteristics to influence large-scale chromosome conformation. Complete insight into the processes that govern the spatial conformation of chromosomes will reveal new mechanisms of gene regulation and may also explain the large amount of non-coding DNA in genomes.
Keywords: boundary element